Cell Surface Binding and Internalization of Aβ Modulated by Degree of Aggregation. (28th December 2010) - Bateman, David A.; Chakrabartty, Avijit
Abstract : The amyloid peptides, A β 40 and A β 42, are generated through endoproteolytic cleavage of the amyloid precursor protein. Here we have developed a model to investigate the interaction of living cells with various forms of aggregated A β 40/42. After incubation at endosomal pH 6, we observed a variety of A β conformations after 3 (A β 3 ), 24 (A β 24 ), and 90 hours (A β 90 ). Both A β 42 24 and A β 40 24 were observed to rapidly bind and internalize into differentiated PC12 cells, leading to accumulation in the lysosome. In contrast, A β 40/42 90 were both found to only weakly associate with cells, but were observed as the most aggregated using dynamic light scattering and thioflavin-T. Internalization of A β 40/42 24 was inhibited with treatment of monodansylcadaverine, an endocytosis inhibitor. These studies indicate that the ability of A β 40/42 to bind and internalize into living cells increases with degree of aggregation until it reaches a maximum beyond which its ability to interact with cells diminishes drastically.